The Complexities of Regional Development Planning Reform: The Indonesian Case - Yeremias T. Keban (Indonesian Association for Public Administration, 2019)
Development planning reform retains a significantly prominent position as it determines the success of development particularly in developing countries. However, implementing development planning reform is no easy feat as various obstacles ensue. This study was conducted in the Yogyakarta Province, Indonesia to identify these specific obstacles through a content analysis of regional development planning documents, provided along with the support of relevant literature study. The results of the study show that the obstacles encountered were quite complex, namely the low capacity of regional government, failure in implementing principles of good governance and bureaucratic reform, and the intensity of political elites’ dominance in the region who utilize development planning as a means of achieving their interests. Affirmative policies to enhance regional capacity, to rearrange regulations and limit political party dominance, and to reconfigure the regional head’s position as a political functionary and personnel administrator are thus recommended to address these issues.